Potential role of the gut microbiota of bumblebee Bombus pyrosoma in adaptation to high-altitude habitats - Zhang, Zhengyi; Guo, Yulong; Zhuang, Mingsheng; Liu, Fugang; Xia, Zhongyan; Zhang, Zhihao; Yang, Fan; Zeng, Huayan; Wu, Yueguo; Huang, Jiaxing; Li, Jilian (Frontiers in Microbiology, 2023)
Gut microbiota affects the health and fitness of bumblebees. Such as gut microbes can expand the host ecological range through their metabolic capacity. However, the diversity of gut microbiota and adaptive functional evolution in high-altitude regions are still unclear. In order to answer how gut microbiota helps the host adapt to high-altitude environments, we analyzed the differences in diversity and function of gut microbiota between high-altitude and low-altitude regions through full-length 16s sequencing. Our results show that High-altitude regions have lower abundance of Fructobacillus and Saccharibacter compared to low-altitude regions. Additionally, some individuals in low-altitude regions were invaded by opportunistic pathogen. Gut microbiota in high-altitude regions have more pathways involved "Protein digestion and absorption", and "Biosynthesis of amino acids" while having fewer Carbohydrate digestion and absorption" and "Salmonella infection". Our finding suggests plateau hosts typically reduce energy metabolism and enhance immunity in response to adverse environments. Correspondingly, the gut microbiota also makes changes such as reducing carbohydrate degradation and increasing protein utilization in response to the host. Additionally, gut microbiota potential regulates their abundance and function to help the host adapt to high-altitude adverse environments.